Analisis Kandungan N-Nitrogen (Amonia, Nitrit, Nitrat) dan Fosfat di Perairan Teluk Pandan Provinsi Lampung - Reza Iklima AS; Gusti Diansyah; Andi Agussalim; Citra Mulia (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Iklima AS et al, 2019. Analysis of N-Nitrogen (Ammonia, Nitrate, and Nitric) and Phosphate at Teluk Pandan’s water territorial, Lampung Province. JLSO 8(1):57-66.Teluk Pandan’s water territorial was known to aquaculture activity such as prawn, pearl oyster and cage culture by community that lived in the area. It activities could makes water quality to be polluted.This research was purposed to known the content of nutrient (Ammonia, Nitrate, Nitric, and Phosphate) and to studied nutrient that related to other’s water quality parametric at Teluk Pandan water territorial. Sampling was determinate by 15station using purposive sampling method. Data analysis was used to studied relation between water quality’s parametric using Principal Component Analysis (PCA). Water sampling was taken at surface using water sampler. It was analyze in Oceanography and Instrumentation Laboratory, Department of Marine Science, Universitas Sriwijaya. Result of this research showing that rate of content nutrient at Teluk Pandan’s water territory ranging from 0.0007-0.0087 mg/L NO3-N, nitric ranging from 0.0001-0.0062 mg/L NO2-N, and phosphate ranging form 0,0012 – 0,0091 mg/L PO4-P. Based on result Teluk Pandan’s water territory still can be used for water’s ecosystem. Result using PCA method showing that correlation between parametric are directly proportional and inversely. Correlation that directly proportional showing by parametric group quadrant I (Temperature, Salinity, Velocity, and Abundance of Phytoplankton), quadrant II (DO, pH and nitrate) and quadrant III (Ammonia, nitric and phosphate). Inversely showing by parametric group quadrant I to parametric group quadrant III.